Clients’ Feedback and Agents’ Performance on Service Delivery and Customer Satisfaction at Company X - Yudelmo, Jupet Seriaco; Pendon III, Fernando; Unico, Maricris; Urbina, Marilou; Bucal, Remedios (International Journal of Research in Interdisciplinary Studies, 2025)
This study investigates the link between Customer Relationship Management (CRM) and service delivery at Company X, a semiconductor firm in Alabang, Philippines. Guided by the SERVQUAL model and using a descriptive-correlational design, the research assessed how agent performance—specifically in understanding client needs, resolving issues, and communicating clearly—affects customer satisfaction across service quality dimensions such as reliability, responsiveness, and assurance. Data were collected from 70 randomly selected clients using a validated questionnaire. Findings indicate that while agents were generally effective, moderate gaps remained in empowerment and communication clarity. Customer satisfaction ratings were positive, particularly in responsiveness and reliability. Significant correlations emerged between agent performance and satisfaction, highlighting the impact of CRM on perceived service quality. The study concludes that enhancing CRM—through targeted agent training, clearer communication, and system improvements—is essential for improving service delivery and sustaining competitive advantage in high-tech industries.